Complete regression of generalized plasmacytoma of lymph nodes in a liver transplant recipient during the conversion of immunosuppressive therapy from tacrolimus to everolimus - V. E. Syutkin; V. R. Gorodetskiy; A. A. Salienko; N. A. Probatova; N. A. Kupryshina; M. S. Novruzbekov (Трансплантология (Москва))
Introduction. One of the serious complications after transplantation of solid organs and bone marrow is the development of post-transplant lymphoproliferative diseases.Clinical case. To evaluate the course of post-transplant lymphoproliferative diseases in the long-term in a liver transplant recipient after conversion of immunosuppressive therapy from tacrolimus to everolimus. We analyze a case of generalized primary plasmacytoma of lymph nodes with bone marrow involvement in a patient after liver transplantation.Results. After conversion of immunosuppression we observed a rapid positive trend: decreasing size of lymph nodes and regression of the level of paraprotein down to its complete disappearance. There were neither adverse events associated with everolimus for four years, nor signs of immunosuppression insufficiency.Conclusion. This Case Report is the first description of a long-term remission of nodal plasmacytoma that developed in a liver transplant recipient after complete withdrawal of calcineurin inhibitors and administration of everolimus. We suggest that the regression of post-transplant lymphoproliferative diseases after replacing calcineurin inhibitors with everolimus is associated not only with the minimization of calcineurin inhibitors exposure, but also with the antitumor effect of the everolimus itself, which prompts us to discuss the possibilities of expanding its clinical application.